Efektivitas Senam Tera terhadap Penurunan Tekanan Darah pada Penderita Hipertensi: Scoping Review - Adiguna, Muhammad Raihan; Sopiah, Popi; Nuryani, Reni (Jurnal Kesehatan Komunitas, 2025)
Hypertension is one of the main causes of cardiovascular disease that currently has a significant increase. One of the treatments for hypertension is a non-pharmacological approach performed with the intervention of tera gymnastics. This review aimed to determine the effectiveness of tera gymnastics in reducing blood pressure in hypertensive patients. A scoping review with PRISMA-ScR guidelines was performed to identify relevant studies from Google Scholar and Semantic Scholar. The inclusion criteria included full-text articles in Indonesian or English, quasi-experimental design, and published by journal institutions from 2015-2024. From six articles included, a diversity of samples, instruments, and interventions was found. Samples were adults to elderly with stage I to stage II hypertension who had measured using aneroid, mercury, and digital sphygmomanometer instruments. These samples were engaged in tera gymnastics sessions 2 to 3 times a week for periods ranging from 1 to 8 weeks. Despite these diverse characteristics, all studies consistently found that tera gymnastics has effectively reduces blood pressure in hypertensive patients.